Pumice Insulation: A Practical Solution for Rural Geothermal Pipelines - Gunnarsdottir, Maria J. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1984)
Geothermal pipelines from heat resistant plastic, insulated with pumice fill, are gaining acceptance in Iceland in rural heating systems. Initial savings with this technique are at least 50% compared with conventional steel piping, but heat losses are relatively high. Ground moisture is a problem, and K-value fluctuates with rainfall levels. Tests conducted by the National Energy Authority demonstrated that this application is practical for rural pipelines, where nearby geothermal sources exist